PENGARUH STRATEGI PEMBELAJARAN REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PAI MATERI FIQH KELAS XI SMA NEGERI 1 PONTIANAK TAHUN AJARAN 2025/2026 - Sulistiawati; M. Alias; Eli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of critical thinking skills in Islamic Religious Education (PAI), particularly in Fiqh material. However, students’ critical thinking skills are still relatively low due to teacher-centered learning processes. One of the learning strategies that can be used to improve students’ critical thinking skills is the REACT learning strategy (Relating, Experiencing, Applying, Cooperating, and Transferring). This study aims to determine the effect of the REACT learning strategy on students’ critical thinking skills in PAI subjects, Fiqh material for grade XI students of SMA Negeri 1 Pontianak in the 2025/2026 academic year. The research method used is a descriptive method with a quantitative approach. The form of the study is an experiment and control using a Quasi-Experimental design with a Pretest-Posttest Control Group Design. The sample consisted of 36 students from class XI A as the control group and 36 students from class XI C as the experimental group. Data collection techniques used a critical thinking skills test. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the Mann-Whitney U Test. The results showed that the average posttest score of the experimental class was 86.00, higher than the control class at 48.23. The Mann-Whitney U Test result obtained an Asymp. Sig. (2-tailed) value of < 0.001, which is smaller than 0.05, so H₀ is rejected and Hₐ is accepted. In addition, the Mean Rank of the experimental class was 46.08, higher than the control class at 20.51. Thus, it can be concluded that the REACT learning strategy has a significant effect on students’ critical thinking skills in PAI subjects, Fiqh material for grade XI students of SMA Negeri 1 Pontianak in the 2025/2026 academic year.